A Study to Evaluate the Effectiveness of Structured Teaching Programme Regarding Control of Anemia and Worm Infestation among Male Adolescents at Madurai (International Journal of Nursing Education, 2022)
Background: The main objective of the study was to evaluate the effectiveness of Structured TeachingProgramme regarding control of anemia and worm infestations among male adolescents at Madurai.Methods and Results : This study was employed at true experimental research design. Totally 60 maleadolescents were included in the study. The study result showed that among control group pretest meanwas 9.86 and standard deviation was 0.54. Post test mean 9.84 and standard deviation 0.60. Differencein mean percentage was 0.02. Worm infection status was same (46.7 % no worm and 53.3 moderateworm load) in pretest and post test without any change. Among experimental group pretest mean was9.84 and standard deviation was 0.60. Post test mean was 12.23 and standard deviation was 1.05.Difference in mean percentage was 2.38. Worm infection status in pretest was 60% moderate wormload and 40 % no worm infection and all participants of experimental group were free from worminfection in post test. The t value was 7.62 and p value of the study was less than 0.001.Conclusion: The structured teaching programme had highly significant on control of anemia and worminfestation among male adolescents